An Analysis of the Threat Factors for the Autonomous Driving Robot on the Construction Site - Kim, Ki-Hyuk; Oh, Chae-Won; Cho, Hyung-Keun; Lee, Donghoon (International Journal of Engineering and Technology, 2018)
Background/Objectives: Construction projects have limitations in improving construction efficiency through mechanization. Therefore, this study aimed to analyze the information needed to apply autonomous driving technology to construction equipment.Methods/Statistical analysis: This study has identified the research trends of big information and autonomous driving technology through existing literature. This study collected information on locations and types of work that require site safety management through a questionnaire survey of experts.Findings:This study focused on the types of information required for autonomous driving in earthwork environment. For this study, experts are engineers who served in the fields of building construction. The result disclosed that radius of operation of construction workers was the most dangerous and entrance of construction site was the least dangerous. Survey result on autonomous driving equipment speed indicated that equipment must come to a full stop within the radius of operation in each hazard area, drive under a normal speed at entrances, and slowdown in all other areas. Regarding potential accidents by autonomous driving equipment, the level of risk was highest for accidents within the range of equipment motion and lowest for equipment collision. When reviewed the result of hazard areas and accidents, it was disclosed that a direct collision between equipment and workers was most hazardous during earthwork. When categorized and analyzed accidents by worker and equipment, there was no significant difference. By the way, there is a difference between proper speeds when passing through workers and equipment.Improvements/Applications: This study can contribute to the automation of the construction site by deriving the information type and the collection method for autonomous driving of the construction equipment.Â Â